Multi-geostatistical analyses of the spatial distribution and source apportionment of potentially toxic elements in urban children's park soils in Pakistan: A risk assessment study. (15th October 2022) - Ghani, Junaid; Nawab, Javed; Faiq, Mohammad Eshaq; Ullah, Sajid; Alam, Arshad; Ahmad, Iftikhar; Ali, Syed Weqas; Khan, Sardar; Ahmad, Imran; Muhammad, Asim; Ur Rahman, Syed Aziz; Abbas, Muhammad; et al.
Abstract: In the past few decades, contamination of urban children's parks (UCPs) with potentially toxic elements (PTEs) has been attracting more and more interest; however, assessment of eco-environmental and child exposure risks particularly in developing countries remains limited. The current study investigated PTE (Cr, Ni, Zn, As, Cd, and Pb) concentrations, potential sources, and their health risk assessment in UCP soils of 12 major cities in Pakistan. The results showed that the mean concentration of Ni exceeded the SEPA-permissible limit in all UCP sites, while other PTEs were found to be within acceptable limits. The soil properties such as pH, electrical conductivity, organic matter, and soil particles size were determined in UCPs soils. The contamination factor and pollution load index results indicated low to moderate pollution levels (CF < 3) and (PLI<1) for all PTEs except Ni in some of the selected cities. Quantile–quantile (Q-Q) plotting determined the normal distribution line for all PTEs in the UCPs. Principal component analysis showed the mixed sources of contamination from industrial emissions, fossil fuel combustion, vehicular emissions, wastewater irrigation, as well as solid waste disposal and natural sources of soil parent materials in all park sites. ANOVA results showed that all the PTEs except Cd had moderate to higher contamination values than the reference site. The risk assessment study revealed that children had high exposure to the selected PTEs via all exposure pathways. The hazard index (HI) mean value (1.82E+00) of Ni for all exposure pathways was greater than 1, while total risk value of Cr (1.00E-03) had exceeded USEPA limit, indicating cancer risk. Consequently, the study of UCPs soils revealed PTEs contamination that could pose a potential health risk to the local population in the studied UCPs regions of Pakistan. Thus, the present study recommends that the influx of PTEs originating from natural and anthropogenic sources should be mitigated and government should implement strict enforcement of environmental regulations and proper management, as well as air quality monitoring guidelines for public health should be strictly adopted to reduce traffic- and industrial emission-related to PTEs in metropolitan areas. Graphical abstract: Image 1 Highlights: Nickel had the highest prevalent contamination in UCPs soils among PTEs. Vehicular and industrial emissions are the main driving factors influencing PTEs. Children were relatively more susceptible than the adults to PTEs exposure in all. UCPs soils. Monitoring strategies should be implemented to mitigate PTEs pollution.